MODEL KERJASAMA PEMBANGUNAN ANTAR DAERAH DALAM RANGKA PENGEMBANGAN WILAYAH PERBATASAN - Mulatto Mulatto; Mursid Zuhri'; YQM Judantoro; Subandriyo Subandriyo; Sunarjan Sunarjan; Teguh Yuwono (JURNAL LITBANG PROVINSI JAWA TENGAH, 2004)
It can be said, that the boundary area less to pay attentionfrom the central administration, so that boundary area condition is not so good. The aim of this study are getting description about development cooperation among Regencies in the boundary area. This study is analytically descriptive, by qualitative and quantitative approaches and used the primary ans secondary data. Data was obtained by interviewing and through questionnaire. The analysis by qualitative analysis and SWOT analysis. The result are indicated that cooperation model can be established among sectors, actors and locations development. In the development sectors indicated that are no cooperation of all over sector, but just only some sectors could be cooperated. The main role of the regional cooperation is the executive body. The cooperation development can be held by Regencies, Sub-regencies (Kecamatan] or Villages.